2015
DOI: 10.1111/are.12705
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community composition of sediments from a milkfishChanos chanosForsskål farm

Abstract: Bacterial communities in sediments underneath milkfish cages and adjacent off‐cage areas in Bolinao, Lingayen Gulf, West Philippine Sea were characterized using PCR‐denaturing gradient gel electrophoresis to assess influence of the fish farming to the sediments. The sediments in the fish cage (FC) area showed anoxic conditions [redox potential of −165 to −213 mV and acid‐volatile sulphide‐sulphur (AVS‐S) of 0.55–1.88 mg g−1 (dry weight)] compared to the relatively oxic off‐cage area [redox potential of 72–81 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…Because this aquaculture mode results in local environmental eutrophication, enclosed aquaculture ponds face severe problems, particularly microbial disease outbreaks (Chifumi et al, 2005 ; Choi et al, 2016 ) and associated impacts on surrounding environments (Sakami et al, 2008 ). In order to solve these problems, an increasing number of studies have focused on the microbial communities in aquaculture environments (Santander-de Leon et al, 2015 ; Dabade et al, 2016 ; Fan et al, 2016 ). However, few reports have explored the correlations between the structure and function of microbial communities and the environmental factors in shrimp cultural enclosure ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Because this aquaculture mode results in local environmental eutrophication, enclosed aquaculture ponds face severe problems, particularly microbial disease outbreaks (Chifumi et al, 2005 ; Choi et al, 2016 ) and associated impacts on surrounding environments (Sakami et al, 2008 ). In order to solve these problems, an increasing number of studies have focused on the microbial communities in aquaculture environments (Santander-de Leon et al, 2015 ; Dabade et al, 2016 ; Fan et al, 2016 ). However, few reports have explored the correlations between the structure and function of microbial communities and the environmental factors in shrimp cultural enclosure ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…The two grow-out plots, namely plot B and plot C, were provided with the same opportunity of two months each for the pond preparation period as previously describedfrom drying to growing natural food. The modular cultivation system employed in this study offers a potential solution to improve the survival and growth rate of milk sh (Santander et al, 2015;Saraswaty et al, 2017;Rinaldi et al, 2019). The construction of modular cultivation system ponds.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with prior research in the eld and highlights the importance of carefully managing the growth and development of milk sh in aquaculture settings (Tsai et al, 1970 The rst cycle recorded a low survival rate of 91%, which can be attributed to the high temperature of 32°C. Previous studies have shown that aquatic organisms, including milk sh, have a range of optimal temperatures that support their survival rate (Ismail et al, 1993;Santander et al, 2015;Ramadhani et al, 2021;Adul et al, 2022). The literature suggests that the high survival rate for milk sh (Chanos chanos) is within the range of 27-31°C, which is consistent with the results obtained by several researchers (Tsai et al, 1970;Lawson, 1995;Garg & Bhatnagar, 2003;Liao et.al, 2004;Bhatnagar, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…(third class of Planctomycetes) were present in the clone library; they perform nitrate-to-nitrite reduction under anaerobic conditions [27], also associated with fermentation at the sulphate-methane transition zone in marine sediments [33]. Species-specific sequence similarity to Spirochaeta genus was observed, which were ubiquitous inhabitants of many aquatic environments [74,88], can colonize and form flocculent matter, and can metabolize carbohydrates [109]. Dehalococcoidaceae (Chloroflexi family) contains dehalogenation complex [122] and is significant indicator of the re-oxidation stage [56].…”
Section: Phylogenetic Analysis Of Bacterial and Archaeal 16s Rrna Genesmentioning
confidence: 99%